What's Your Excuse? Sensemaking About Chronic Absenteeism in a Rural, Latinx High School. Issue 4 (July 2022) - Grooms, Ain A.; Bohorquez, Diana Galvez
Nationwide, over seven million students are chronically absent from school each year, impacting academic success and future job earnings. Latinx high school students have among the highest absentee rates across all racial groups. Using critical sensemaking theory, this qualitative case study examines how school, district, and community leaders make sense of chronic absenteeism in their diversifying local high school. This study is situated in Hensonville Secondary School (a pseudonym), a small, rural high school in Iowa serving a predominantly Latinx student body. Findings reveal that persistent deficit narratives placed upon Latinx and/or low-income students drive the perception of absentee students as "others" that do not fit the expectations of the educational leaders or of the broader community. Power and privilege in the district were evident as white educational leaders blamed Latinx students and those from low-income backgrounds for chronic absenteeism while minimizing the institutional and contextual factors that may be contributing to low student attendance. Collaborative partnerships are increasingly being used to address chronic absenteeism, and we also investigate these efforts in Hensonville. white educational leaders in diversifying rural communities, and the leadership preparation programs educating these future leaders, must rely on culturally relevant/responsive strategies in order to best support their students and reduce chronic absenteeism.